Early Removal of Drainage Tube after Fast-Track Primary Total Knee Arthroplasty - Zhang, Shaoyun; Xu, Bin; Huang, Qiang; Yao, Huan; Xie, Jinwei; Pei, Fuxing (The Journal of Knee Surgery, 2017)
There is no consensus as to whether drainage tube should be used and how long it should remain in use after primary total knee arthroplasty (TKA). As fast-track (FT) program has been implemented in TKA, whether drainage tube could be removed early, and the ideal timing for removal after FT primary TKA has been a new topic. The purpose of this prospective cohort study was to evaluate the safety and feasibility of early removal of drainage tube when FT program was implemented in primary TKA. A total of 101 patients undergoing FT primary TKA were prospectively allocated into three groups. Patients in group A (31 patients) indwelled wound drainage tube for 6 hours after surgery while group B (34 patients) for 12 hours and group C (36 patients) for 18 hours. The knee circumference, resting and moving visual analogue score (VAS), hemoglobin (Hb), hematocrit, white blood count (WBC), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), interleukin-6 (IL-6), the volume of blood loss and drainage, and postoperative length of stay (LOS) among three groups were recorded and compared. There was no statistically significant difference in the volume of total and hidden blood loss among three groups (p > 0.05), but as the time of drainage prolonged, total volume of drainage and dominant blood loss increased gradually (p < 0.01). The knee circumference, the mean of resting and moving VAS, Hb, WBC, ESR, CRP, and IL-6 of three groups were similar preoperatively and on postoperative day 1 and 3 (p > 0.05), the decrease of Hb in the perioperative period and postoperative LOS as well. Early removal of wound drainage tube could drain the hematocele and reduce the risk of infection, and it doesn't increase the sense of pain, inflammatory reaction, limb swelling, and total blood loss. It's safe and feasible to remove the drainage tube within 6 to 12 hours after FT primary TKA.
Keywords: total knee arthroplasty; drainage tube; fast-track program; tranexamic acid